2020
DOI: 10.1186/s12885-020-07014-w
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tripartite motif-containing 44 and its prognostic and clinicopathological value in human malignancies:a meta-analysis

Abstract: Background: Previous researches have reported that tripartite motif-containing 44 (TRIM44) is related to the prognosis of multiple human tumors. This study was designed to systematically assess the prognostic value of TRIM44 in human malignancies and summarize its possible tumor-related mechanisms. Methods: The available databases were searched for eligible studies that evaluated the clinicopathological and prognostic roles of TRIM44 in patients with malignancies. The hazard ratios (HR) and odds ratios (OR) we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…PRKAR2A is a camp-dependent type II regulatory subunit of protein kinase, and studies have shown that its expression is related to colorectal cancer, adipocyte differentiation, and other processes ( Spracklen et al., 2019 ). It was found that the mRNA expression level of Trim44 in most malignant tumor tissues was higher than that in corresponding normal tissues ( Xiao et al., 2020 ). Sash1 is an adaptor and signal transduction protein, which is considered as a tumor suppressor ( Ilnitskaya et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…PRKAR2A is a camp-dependent type II regulatory subunit of protein kinase, and studies have shown that its expression is related to colorectal cancer, adipocyte differentiation, and other processes ( Spracklen et al., 2019 ). It was found that the mRNA expression level of Trim44 in most malignant tumor tissues was higher than that in corresponding normal tissues ( Xiao et al., 2020 ). Sash1 is an adaptor and signal transduction protein, which is considered as a tumor suppressor ( Ilnitskaya et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…TRIM44 is localized in the cytoplasmic compartment, contributing to diverse pathological conditions like tumors, growth disorders, and neurodegeneration ( Xiao et al 2020 ). TRIM44 is an atypical TRIM family protein that lacks the RING-finger domain but harbors a zinc-finger domain that is often found in ubiquitin-specific proteases (USPs).…”
Section: Rna-binding Protein Partners Of Rna Sensorsmentioning
confidence: 99%
“…Interestingly, in addition to known cardiac TRIMs, several other TRIMs were found to be differentially regulated in these disease conditions, and the expression of TRIM44 was increased under all the pathological conditions mentioned above. Accumulating evidence has shown that dysregulation of TRIM44 protein is associated with several diseases, such as cancer, developmental disorders, neurodegenerative disease, viral infection and aniridia ( Yang et al, 2013 ; Yamada et al, 2020 ; Xie et al, 2021 ; Wei et al, 2019 ; Xiao et al, 2020 ; Peng et al, 2018 ; Li et al, 2018 ; Liu et al, 2018 ; Yu et al, 2021 ; Kashevarova et al, 2014 ; Zhang et al, 2015a ; Samant et al, 2016 ; Lim et al, 2017 ; Landsend et al, 2018 ). Borlepawar et al’s analysis of upregulated expression of TRIM44 in cardiac pathology suggests that it may be involved in the regulation of cardiovascular pathological processes.…”
Section: Introductionmentioning
confidence: 99%